2023
DOI: 10.1177/00938548231208203
|View full text |Cite
|
Sign up to set email alerts
|

Moral Injury as a Transdiagnostic Risk Factor for Mental Health Problems in Detained Youth

Ava R. Alexander,
Lucybel Mendez,
Patricia K. Kerig

Abstract: Youth who become involved in the juvenile justice system are at highly elevated risk for many emotional and behavioral problems. Past research has often focused on trauma exposure as a transdiagnostic risk factor in this population. However, distress resulting from perpetrating or witnessing acts that conflict with one’s deeply held moral beliefs, termed moral injury, may also play a role in predisposing these youth toward negative mental health outcomes. This study utilized a sample of 96 youth housed in secu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…The effect of exposure to potentially morally injurious events on the mental health outcomes of juveniles involved in the juvenile justice system is examined and it indicates that, even after adjusting for trauma exposure and demographic variables, PMIEs are strongly linked to symptoms of depression, anxiety, and non-suicidal self-injury (NSSI). The study has implications for both research and clinical practice, emphasizing the significance of taking moral harm into account while comprehending and resolving mental health difficulties in this community (Alexander et al, 2024).…”
Section: Mental and Psychological Factormentioning
confidence: 99%
“…The effect of exposure to potentially morally injurious events on the mental health outcomes of juveniles involved in the juvenile justice system is examined and it indicates that, even after adjusting for trauma exposure and demographic variables, PMIEs are strongly linked to symptoms of depression, anxiety, and non-suicidal self-injury (NSSI). The study has implications for both research and clinical practice, emphasizing the significance of taking moral harm into account while comprehending and resolving mental health difficulties in this community (Alexander et al, 2024).…”
Section: Mental and Psychological Factormentioning
confidence: 99%
“…Finally, Hall et al.’s (2022) systematic review of PMIE exposure and mental health research identified no studies that tested moderators of the association between PMIEs and anxiety symptoms. Given the increasing attention to moral injury as a potentially transdiagnostic factor influencing mental health more generally (e.g., Alexander et al., 2024), an exploration of potential moderators of the impact of PMIE exposure on other diagnoses (e.g., depression, general anxiety) is warranted.…”
mentioning
confidence: 99%